2006
DOI: 10.1359/jbmr.060208
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Isoflavone and Exercise on BMD and Fat Mass in Postmenopausal Japanese Women: A 1-Year Randomized Placebo-Controlled Trial

Abstract: The combined intervention of isoflavone intake and walking exercise over 1 year in postmenopausal Japanese women exhibited a trend for a greater effect on prevention of bone loss at the total hip and Ward's triangle regions. Introduction:The additive effects of isoflavones and exercise on bone and lipid metabolism have been shown in estrogen-deficient animals. In this study, we determined the effects of isoflavone intake, walking exercise, and their interaction on bone, fat mass, and lipid metabolism over 1 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
117
1
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(125 citation statements)
references
References 45 publications
5
117
1
2
Order By: Relevance
“…(17) Very few randomized controlled trials on soy isoflavones effects on bone have contained data for bCTX and P1NP, and those reported have generally not detected significant effects of soy isoflavone supplements on these bone turnover markers. (18) The heterogeneity of trial results are likely to be a combination of underpowered clinical trials and differences in habitual dietary intake of soy isoflavones, (19) the variable interval since the onset of menopause, (20) as well as the chemical forms and proportions of individual soy isoflavones. (21) The current study sought to minimize these variables by investigating a homogeneous large study population of women who were likely to be at maximal bone turnover by being within the first 2 years of their menopause.…”
Section: Discussionmentioning
confidence: 99%
“…(17) Very few randomized controlled trials on soy isoflavones effects on bone have contained data for bCTX and P1NP, and those reported have generally not detected significant effects of soy isoflavone supplements on these bone turnover markers. (18) The heterogeneity of trial results are likely to be a combination of underpowered clinical trials and differences in habitual dietary intake of soy isoflavones, (19) the variable interval since the onset of menopause, (20) as well as the chemical forms and proportions of individual soy isoflavones. (21) The current study sought to minimize these variables by investigating a homogeneous large study population of women who were likely to be at maximal bone turnover by being within the first 2 years of their menopause.…”
Section: Discussionmentioning
confidence: 99%
“…Wu et al studied the effects of isoflavone intake, walking exercise and their interaction on lipid metabolism over 1 year in postmenopausal Japanese women [15]. A total of 136 postmenopausal women at < 5 years after the onset of menopause were randomly assigned to four groups: placebo, walking (45 min/day, 3 days/week) with placebo, isoflavone intake (75 mg of isoflavone conjugates/day), and combination of isoflavone plus walking.…”
Section: Wu Et Al [15]mentioning
confidence: 99%
“…All were conducted in post-menopausal women, but were very heterogeneous regarding mean age, years since last menses, and bone status. Isoflavones were consumed in capsules in eight studies, either extracted from soy germ Wong et al, 2009), from soy beans/protein Huang et al, 2006;Levis et al, 2011), from an undisclosed source (Wu et al, 2006b), or provided as pure genistein from undisclosed origin Morabito et al, 2002). Soy isoflavones were consumed as part of soy foods (e.g.…”
Section: Maintenance Of Bone Mineral Density (Id 1655)mentioning
confidence: 99%
“…Four studies each reported a statistically significant change in BMD at only one bone site among a number of sites measured (whole body (Wong et al, 2009); intertrochanter region of the hip (Kreijkamp-Kaspers et al, 2004); femoral neck ); Ward's triangle (Wu et al, 2006b)) in the soy isoflavone group compared to placebo, with no significant changes in markers of bone formation or resorption. The bone site at which a significant effect of soy isoflavones was reported was never the primary outcome of the study and differed between studies.…”
Section: Maintenance Of Bone Mineral Density (Id 1655)mentioning
confidence: 99%
See 1 more Smart Citation